2010
DOI: 10.1111/j.1365-2966.2010.17297.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass profiles and galaxy orbits in nearby galaxy clusters from the analysis of the projected phase space

Abstract: We analyse kinematic data of 41 nearby (z < 0.1) relaxed galaxy clusters in terms of the projected phase‐space density using a phenomenological, fully anisotropic model of the distribution function. We apply the Markov Chain Monte Carlo approach to place constraints on total mass distribution approximated by the universal Navarro, Frenk and White (NFW) profile and the profile of the anisotropy of galaxy orbits. We find the normalization of the mean mass–concentration relation is c= 6.9+0.6−0.7 at the virial ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
92
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 85 publications
(215 reference statements)
17
92
1
Order By: Relevance
“…Kinematical modelers attempt to throw out the high-velocity interlopers by identifying this gap by eye (Kent & Gunn 1982;Łokas & Mamon 2003) or automatically (Fadda et al 1996) or by rejecting 3σ outliers, either using a global criterion (Yahil & Vidal 1977) or a local one (e.g. Łokas et al 2006;Wojtak & Łokas 2010). Interestingly, the 3σ v criterion was first motivated on statistical grounds, but the v 2.0 v v inflection point one sees in the plots of Fig.…”
Section: Global Statisticsmentioning
confidence: 99%
“…Kinematical modelers attempt to throw out the high-velocity interlopers by identifying this gap by eye (Kent & Gunn 1982;Łokas & Mamon 2003) or automatically (Fadda et al 1996) or by rejecting 3σ outliers, either using a global criterion (Yahil & Vidal 1977) or a local one (e.g. Łokas et al 2006;Wojtak & Łokas 2010). Interestingly, the 3σ v criterion was first motivated on statistical grounds, but the v 2.0 v v inflection point one sees in the plots of Fig.…”
Section: Global Statisticsmentioning
confidence: 99%
“…Several X-ray and other studies studies have found that the mass of A2142 is approximately M = 0.9 × 10 15 h −1 M (Okabe & Umetsu 2008;Umetsu et al 2009;Wojtak & Łokas 2010;Munari et al 2014;Shan et al 2015). Munari et al (2014) compared several mass estimation methods and concluded that the mass of the cluster is M 200 = 0.875 × 10 15 h −1 M (if recalculated to the Hubble parameter H 0 = 100 h km s −1 Mpc −1 , as used in our paper); this value is 0.965 times lower than the dynamical mass of A2142 as calculated in Tempel et al (2014b).…”
Section: Abell Cluster A2142mentioning
confidence: 99%
“…Observational constraints on the spherical anisotropy β in individual clusters exhibit a huge variety of profiles (Benatov et al 2006;Hwang & Lee 2008;Wojtak & Lokas 2010;Wojtak et al 2009). Some measurements are far outside the margins allowed by the spherically averaged profiles of simulated clusters (see e.g.…”
Section: Observational Constraints On βmentioning
confidence: 99%
“…It plays a key role in dynamical modelling of kinematical data of objects at all scales, from the stellar halo of the Milky Way (Kafle et al 2012), dwarf spheroidals ( Lokas 2009;Walker et al 2009), to elliptical galaxies (Dekel et al 2005;Napolitano et al 2011;Wojtak & Mamon 2012) and galaxy clusters (Biviano & Girardi 2003;Wojtak & Lokas 2010). Prior knowledge on the anisotropy or elaborated techniques of data analysis are essential for accurate and unbiased mass estimates.…”
Section: Introductionmentioning
confidence: 99%